2018
DOI: 10.4236/oalib.1104684
|View full text |Cite
|
Sign up to set email alerts
|

Student-Centered Teaching Approach Combined with Coaching and Mentoring Elements in Arabic Language Speaking Proficiency

Abstract: The acquisition of Arabic speaking skills becomes an important issue in Arabic language learning. So, the National University of Malaysia (UKM) has offered the PPPJ3503 Oral Arabic Language Course as one of the department's elective subjects to undergraduate degree students. The purpose of this study is to evaluate the proficiency of speaking in Arabic and identify improved language-speaking factor among students. This research was a quantitative case study using data from survey instruments and focus group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One of the challenges of getting students to master and become fluent in a language is getting students to do practise combined with coaching and mentoring elements, as stated by Yaacob, M. and Bakar, K.A. (2018).…”
Section: Problem Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges of getting students to master and become fluent in a language is getting students to do practise combined with coaching and mentoring elements, as stated by Yaacob, M. and Bakar, K.A. (2018).…”
Section: Problem Statementsmentioning
confidence: 99%
“…Engaging students in practise will increase their understanding and confidence in the Arabic course and prevent them from being bored when they take the course, as noted by Arifin, Z. et al (2021). Coaching is an important element in language learning as noted by Yaacob, M. and Bakar, K.A. (2018).…”
Section: Coaching All Students In Classmentioning
confidence: 99%
“…This assertion is believed to be consistent with research by Nadwah and Nadhilah (2014) that demonstrates that although students majoring in Arabic at universities will go on to become Arabic teachers after graduation, more than 69 percent of students have only rudimentary proficiency in speaking Arabic. The lack of vocabulary linked to the topics the students want to speak about as well as their anxiety about making mistakes while speaking Arabic are the main causes of the students' inferior speaking abilities (Yaacob & Bakar 2018). In addition, the setting and the environment for learning foreign languages in Malaysia are still quite inadequate (Klein, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The above scenario applies to the teaching and learning of most second languages including the Arabic language. However, previous studies have also shown that non-native Arabic learners outside the Arab countries are at the disadvantage due to the limited real life encounters of the Arabic environment in the process of teaching and learning (Rohaizaf, 2013;Yaacob & Bakar, 2018). This causes the absence of practical application by learners after leaving the classroom.…”
Section: Introductionmentioning
confidence: 99%